Pro SQL Server 2012 BI solutions - Root, Randal (Expert's voice in SQL server., 2012)
Business intelligence projects do not need to cost multi-millions of dollars or take months or even years to complete! Using rapid application development (RAD) techniques along with Microsoft SQL Server 2012, this book guides database administrators, SQL programmers, and report specialists in creating practical, cost-effective business intelligence solutions for their companies and departments. Pro SQL Server 2012 BI Solutions provides practical examples of cost-effective business intelligence projects. Readers will be guided through several complete projects that build a foundation for real-world solutions. Even with limited experience using Microsoft's SQL Server, Integration Server, Analysis Server, and Reporting Server, you can leverage your existing knowledge of SQL programming and database design to provide users with the business intelligence reports they need. Provides recipes for multiple business intelligence scenarios Progresses from simple to advanced projects using several examples Shows Microsoft SQL Server technology used to complete real-world business intelligence projects.